2021
DOI: 10.1108/jmhtep-04-2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and online learning among medical students during the COVID-19 pandemic: a Saudi national study

Abstract: Purpose The coronavirus disease (COVID-19) pandemic has multiple consequences, including social distancing and the shift of education from in-person to online learning, which may have a psychological impact on students, especially those in medical colleges. This study aims to explore the effect of online learning on medical students’ mental health during the COVID-19 pandemic across Saudi Arabia. Design/methodology/approach A descriptive, nationwide, cross-sectional survey was conducted during the COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
4
18
0
Order By: Relevance
“…The main findings showed that female gender can be considered as one of the risk factors associated with an increased probability of somatic complaints and anxiety in both countries, and depression in the Czech Republic. This is in line with other studies focusing on students' mental health ( 9 , 14 , 39 , 46 49 ). It is a well-known fact that females are more prone to mental disorders and report more mental health problems compared to their male counterparts ( 50 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The main findings showed that female gender can be considered as one of the risk factors associated with an increased probability of somatic complaints and anxiety in both countries, and depression in the Czech Republic. This is in line with other studies focusing on students' mental health ( 9 , 14 , 39 , 46 49 ). It is a well-known fact that females are more prone to mental disorders and report more mental health problems compared to their male counterparts ( 50 ).…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also shown that academic years play an important role in students' mental health. In this regard, AlJhani et al ( 14 ) confirmed that first-year students from Saudi Arabia had higher levels of anxiety and stress. Al Saadi et al ( 71 ) found that anxiety was less likely in fifth-and sixth-year compared to second-year students.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations